Biological N₂ fixation and N loss as N₂O and N₂ in a white clover-based system of dairy production - Burchill, William (Trinity College (Dublin, Ireland). Department of Botany, 2014)
Pasture-based livestock production systems have a relatively large requirement for nitrogen (N) input compared to other food production systems. These inputs may consist of organic N, mineral N or biologically-fixed N. Of all N that enters these systems, only a small proportion (15-40%) is converted to saleable agricultural products. The remaining N (surplus N) is largely unaccounted for and can be either lost from the system through a range of pathways including gaseous N losses to the atmosphere as nitrous oxide (N2O), ammonia (NH3), and dinitrogen (N2), N losses to groundwater or N may be immobilised in soil organic matter, all of which have differing environmental consequences.
Keywords: Botany, Ph.D.; Ph.D. Trinity College Dublin